Pengaruh Pemikiran Ulama Dinasti Abbasiyah Terhadap Kemajuan Pendidikan Islam di Era Modern: The Influence of Abbasid Thought on the Progress of Islamic Education in the Modern Era - Diah Novita Fardani (ISEDU : Islamic Education Journal, 2024)
A pivotal point in Islamic history, the Abbasid Dynasty (750-1258 CE) saw remarkable advances in intellectual thought, knowledge, and culture. The foundation of Islamic culture was shaped by the enduring contributions of scholars of this era in the fields of philosophy, science, law, art, and spirituality. Imam Abu Hanifa, Imam Malik, Imam Shafi'i, and Imam Ahmad ibn Hanbal were influential in the development of Islamic jurisprudence, and scholars such as Al-Kindi, Al-Farabi, and Ibn Sina advanced human understanding by blending Islamic doctrines with Greek philosophy. Through academics such as Imam Ghazali, the Abbasid Dynasty also encouraged the development of art, culture, and spirituality, which had an impact on the Islamic reform and revival movements. Islamic science is increasingly strengthened by the establishment of educational institutions, which gave birth to generations of insightful and competent. These contributions demonstrate the enduring influence of the intellectuals of the Abbasid era on the development of Islam in the modern era and continue to influence contemporary Islamic thought.